The Factors Influencing the Decision of the Syrian Refugee in Jordan to Return to Home Country (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
This study investigated the degree of impact of each of the social, economic and security factors on the decision of the Syrian refugees in Jordan to return to their home country. Using the descriptive analytical approach, 357 electronic questionnaires were distributed to the study samples, who are Syrian refugees in Jordan whose ages are over 18 The results of the study indicate that the degree of influence of social, economic and security factors was generally medium, and that security factors had a high impact and were among the most important factors that influence the decision of Syrian refugees to return to their homeland; they felt that their country lacks security and stability. The economic factors came to a moderate degree; the factor of their professional or occupational success and their private or joint business with Jordanians in the country of asylum was a decisive factor in the decision to return to their country. As for the social factors, which came to a medium degree as well; the factor that they established a new life, that they formed a family in the country of asylum, and that they coexisted and integrated with Jordanians prevented them from returning to their country of origin.
Keywords: Syrian Refugee; Voluntary Return; Coexistence; Integration